FINITE DIFFERENCE METHOD FOR CALCULATING OF THE GAS FLOW IN A SUBSONIC GAS EJECTOR - Kapitanchuk, Kostjantin; Grekov, Pavlo; Bohdanov, Mykola; Nikitina, Galina (Proceedings of National Aviation University (archive), 2016)
Describe analysis of eddy viscosity actual mathematical models for numerical simulation a reversal gas flow in subsonic gas ejector. Considered advantages and disadvantages each of it. Proposed use method of finite elements for provides viscous gas flow calculation of gas ejectors.